‘NISKAMA KARMA’ SEBUAH AJARAN KARMA YANG MEMBEBASKAN - Gusti Ngurah Yoga Semadi; I Made Dwija Suastana (Veda Jyotih: Jurnal Agama dan Sains, 2023)
Niskama Karma is a teaching concept which can be interpreted as actions that are without lust or not because of lust or without desire Karma or actions and niskama are without desire, thus niskama karma means actions without desire. Nis means no, which is not based on worldly desires. This karma or liberating action is very pure, blameless, and also selfless on the basis of the teaching of selfless work. Human nature is basically to have the nature of love, compassion. Carrying out work without attachment to the results of the work is the key to this teaching. This work becomes liberating work, where actions that are based without desire for the results of the fruit that are carried out are work that is based on applying the work concept of ‘niskama karma’, namely by simply doing ‘selfless work’. If work is based on selflessness, then grace will automatically come without being sought. The grace in question is the abundant blessing from the ruler of the universe. This is a condition of the human psyche that makes him achieve true peace so that ideas that are full of holiness and goodness appear. The sense of peace appears instantly if humans have felt and received protection from God.